PENGARUH KEPUTUSAN BUYBACKSELAMA PANDEMI COVID 19 TERHADAP PERUBAHAN HARGA SAHAM (STUDI KASUS PADA PT RAMAYANA LESTARI SENTOSA TBK) - Tri Handayani; Priscilla Iranata Panjaitan; Nur Hanifah; Indah Agustina (Jurnal Kompetitif Bisnis, 2020)
Covid-19 virus that is attacking Indonesia has caused economic turmoil in Indonesia. This study aims to determine whether there is an influence of the buyback decision during the covid pandemic 19 on changes in stock prices (case study at PT Ramayana Lestari Sentosa, Tbk). The study uses descriptive research methods to thoroughly describe the problems that occur and relate to the buyback decision made by PT Ramayana Lestari Sentosa, Tbk during this co-19. In this study secondary data, namely the daily stock price data of PT Ramayana Lestari Sentosa, Tbk, were taken from stock trading on IDX.co.id. List of stock prices taken from March 16-18, 2020 to see the movement of stock prices before and after the announcement of buy back from PT. Ramayana Lestari Sentosa, Tbk. The results of this study are the stock price of PT. Ramayana Lestari Sentosa, Tbk continued to experience a decline from before and after the Buyback announcement. Because investors respond negatively to this buyback because they assume that the business in the retail sector is not very good in this co-19 condition. PT. Ramayana Lestar Sentosa changes other business strategies to increase the number of shares purchased so that the price of PT. Ramayana Lestari Sentosa can rise again.